1993
DOI: 10.1111/j.1600-0447.1993.tb03419.x
|View full text |Cite
|
Sign up to set email alerts
|

A twin study of DSM‐III‐R anxiety disorders

Abstract: The prevalence of anxiety disorders was studied in a sample of 20 monozygotic (MZ) and 29 dizygotic (DZ) co-twins of anxiety disorder probands. A comparison group of co-twins of 12 MZ and 20 DZ twin probands with other non-psychotic mental disorders was also studied. All subjects were personally interviewed with the Structured Clinical Interview for DSM-III-R Axis I (SCID-I). Panic disorder was significantly more prevalent in co-twins of panic probands. Generalized anxiety disorder (GAD) was more prevalent in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
74
0
4

Year Published

1997
1997
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(78 citation statements)
references
References 17 publications
(8 reference statements)
0
74
0
4
Order By: Relevance
“…Family and twin studies have suggested etiological genetics in panic disorder, [10][11][12][13] and are commonly found with high frequency in mood disorder pedigrees. 14 In addition, high frequency of comorbidity between mood disorders and panic disorder is well recognized.…”
Section: Introductionmentioning
confidence: 99%
“…Family and twin studies have suggested etiological genetics in panic disorder, [10][11][12][13] and are commonly found with high frequency in mood disorder pedigrees. 14 In addition, high frequency of comorbidity between mood disorders and panic disorder is well recognized.…”
Section: Introductionmentioning
confidence: 99%
“…A number of family studies (e.g., Fyer, Mannuzza, Chapman, Liebowitz, & Klein, 1993;Lieb et al, 2000), twin studies (Skre, Onstad, Torgersen, Lygren, & Kringlen, 1993), and high-risk studies (Mancini, van Ameringen, Szatmariu, Fugere, & Boyle, 1996) suggest that SAD is genetically transmitted, especially the generalized subtype of SAD (Mannuzza et al, 1995;Stein et al, 1998). For example, a direct-interview family study estimated the relative risks for generalized SAD to be 10-fold greater among first-degree relatives of probands with generalized SAD than among first-degree relatives of non-anxious controls (Stein et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…6 Family studies have consistently shown a higher prevalence ranging from between 7.7% to 20.5% in first-degree relatives of probands. 6 Twin studies have shown concordance rates of 25% for MZ twins and 10% for DZ twins, 7 suggesting a genetic component in the development of this disease.…”
mentioning
confidence: 99%